Clearance of carbonyl-modified lipoproteins from the bloodstream of rabbits - M. A. Grechnikova; S. P. Domogatskiy; G. G. Konovalova; A. K. Tikhaze; V. Z. Lankin (Acta Biomedica Scientifica, 2016)
We have suggested that the molecular mechanism of vascular wall damage in diabetes is not substantially different from that in atherosclerosis. Thus, it can be assumed that aldehyde-modified LDL should be eliminated from the blood stream with much greater speed than non-oxidized LDL. In the available literature there is information about the clearance of native human LDL from the bloodstream, whereas information on the clearance of the aldehyde-modified LDL in animals or humans was not found. Based on this, the present work is devoted to the clearance of aldehyde-modified LDL of rabbits and humans introduced into the bloodstream of rabbits. We investigated the clearance of glyoxal-, methylglyoxal- and MDA-modified LDL from the bloodstream of rabbits. We used biotinylated LDL of rabbit blood plasma and FITC-labeled LDL of human blood plasma. LDL was isolated with preparative ultracentrifugation in NaBr gradient. It was shown that glyoxal- and methylglyoxal-modified LDL of rabbits and humans circulated in the bloodstream for the same time as native LDL while MDA-modified LDL was rapidly eliminated from the bloodstream. The data obtained indicated the possibility of greater atherogenic potential of glyoxal- and methylglyoxal-modified LDL as they circulate in the bloodstream for a rather long time. At the same time, MDA-modified LDL is likely to be exposed to enhanced elimination by macrophages after their "linkage" to blood cells.